KINEMATIC AND ANALOG MODELING OF 3-D EXTENSIONAL RAMPS: OBSERVATIONS AND A NEW 3-D DEFORMATION MODEL - Medwedeff D.A.; Krantz R.W. (My University, 2002)
We present results of kinematic and dry-sand analog models of hanging wall folding over an extensional ramp-flat system containing complementary strike bends. The kinematic models illustrate that differential structural relief is controlled by changes in apparent fault dip in the displacement direction. Variation in 'inclined-shear' angle modifies the magnitude, but not the sign, of this differential relief.In a novel analog modeling method, we create a weak fault zone by coating the entire rigid footwall (ramps and flat) with a thin layer of silicone putty below a dry sand hanging wall. At low strain rates, the silicone polymer is weaker than the dry sand and thus provides a good fault zone analog. A 3° tilt is sufficient to induce displacement, and all deformation is driven by gravity. In the models, we observe that hanging wall displacements near the oblique segment of the ramp are deflected toward the ramp strike.Oblique inclined-shear, a new quantitative geometric model, explains the bending of displacement paths towards the strike, rather than the dip, of oblique ramp segments. The model is conceptually equivalent to 2-D, inclined-shear models in which the hanging wall is imagined to pull rigidly away from and then collapse against the footwall. Because gravity is the driving force, antithetic collapse is directed normal to the incipient void, which introduces a component of slip normal to the fault strike. Vector sum of the normal component with the regional component results in the observed displacement.
Keywords: KINEMATIC MODEL; ANALOG MODEL; EXTENSIONAL RAMP